(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, the fast food chain is the most popular restaurant today, and that’s why many people eat here because of the affordable price and high service quality to provide the customer needs. There are various types of fast food restaurants, and each of them has a unique specialization to satisfy their customers. In this generation, many students have worked in fast-food chains to earn money and support their studies. Working in fast food is a good way to gain experience and meet different types of people. Being a working student is a responsibility because they have to divide their time between study and work. Living as a working student is stressful, most likely balancing their social life, time for family and friends, and also things that they want to do in their lives. Based on the results of the study, most working students struggle to balance their work and study, which leads to stress and poor performance. Working with students is really a hassle. There’s so much struggle, especially how to manage their time. They should have set priorities and have proper schedules to fulfill all the responsibilities between school and work, and they also need to have self-discipline when it comes to managing the time they have to balance their stress.